2017
DOI: 10.1111/geb.12605
|View full text |Cite
|
Sign up to set email alerts
|

Linking species interactions with phylogenetic and functional distance in European bird assemblages at broad spatial scales

Abstract: Aim Understanding the relative contribution of different species interactions in shaping community assembly has been a pivotal aim in community ecology. Biotic interactions are acknowledged to be important at local scales, although their signal is assumed to weaken over longer distances. We examine the relationship between positive, neutral and negative pairwise bird abundance distributions and the phylogenetic and functional distance between these pairs after first controlling for habitat associations. Locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…existence of basal niche overlap) suggesting that interspecific competition plays a dominant role in shaping large‐scale abundance patterns, and our empirical findings provide a clear support. Therefore, although interspecific competition may be not a dominant driver of community‐wide patterns (but see Gotelli, Graves, & Rahbek, ), it is important for limitation of closely related species’ pairs (see also Mönkkönen, Devictor, Forsman, Lehikoinen, & Elo, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…existence of basal niche overlap) suggesting that interspecific competition plays a dominant role in shaping large‐scale abundance patterns, and our empirical findings provide a clear support. Therefore, although interspecific competition may be not a dominant driver of community‐wide patterns (but see Gotelli, Graves, & Rahbek, ), it is important for limitation of closely related species’ pairs (see also Mönkkönen, Devictor, Forsman, Lehikoinen, & Elo, ).…”
Section: Discussionmentioning
confidence: 99%
“…Do these studies imply that the interspecific competition is in- Gotelli, Graves, & Rahbek, 2010), it is important for limitation of closely related species' pairs (see also Mönkkönen, Devictor, Forsman, Lehikoinen, & Elo, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that species tend to have the highest temporal occupancy in environments that are closest to their range-wide environmental centroids, with decreasing temporal occupancy in environments that are most different from the centroid conditions. Overall, temperature had the strongest effect on temporal occupancy of the environmental vari- Ecologists increasingly recognize that biotic factors may also be important in shaping distributions over broad geographic scales (Araújo & Rozenfeld, 2014;Belmaker et al, 2015;Bruno et al, 2003;Mönkkönen et al, 2017). Even though abiotic variables generally explained more variance in temporal occupancy, the maximum amount of variance that could be explained by competitor abundance (48% for yellow-bellied sapsucker, Sphyrapicus varius) was greater than the maximum amount of variance that could be explained by the environment (43% for bushtit).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding what factors limit species distributions is critical for determining why species persist in their range and what habitat conditions they require (Andrewartha & Birch, 1954;Brown, 1984;Case, Holt, McPeek, & Keitt, 2005;Franklin, 2010;Guisan & Thuiller, 2005). Traditionally, species' distributions have been modelled based on presence/absence (Elith et al, 2006;Ferrier, Drielsma, Manion, & Watson, 2002;Phillips, Anderson, & Schapire, 2006) or as a snapshot in time of spatial abundance patterns (Bahn & McGill, 2007;Mönkkönen, Devictor, Forsman, Lehikoinen, & Elo, 2017). An alternative measure of occurrence is temporal occupancy, often measured as the proportion of years a species was observed at a given sampling site over time (Coyle, Hurlbert, & White, 2013;Snell Taylor, Evans, White, & Hurlbert, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…has rarely been explored [7][8][9]. Thus, incorporating multispecies interactions in biodiversity response models is still challenging, although it would improve our understanding of large-scale biodiversity patterns when compared with classical studies focusing on single taxa [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%